Willingness to pay for improving water quality: a contingent valuation study on selected rivers, Dhaka - Islam, Md. Ariful (2019)
The improvement of river water quality has been recognized as a means of achieving successful river restoration that shows improved morphological and biota conditions. Since the restoration of river is synonymous with high cost, a debate has emerged on the meaningfulness of such investments which underlie the gap between anticipations of policy-makers and societal preferences. Using double-bounded dichotomous contingent valuation method, this study explores public awareness, attitude and perception regarding environmental and water resource issues and assessed the preference heterogeneity and willingness to pay (WTP) for two levels of water quality improvement namely, fishable and swimmable (higher) levels. Various rankings, Likert scales, Logit, Probit, and Modified Ordered Probit models were used to analyze the data. A total of 734 samples were collected from two separate contingent valuation surveys to acquire the WTP for Buriganga river (n = 436) and WTP for three rivers (n = 298) from the respondents of Dhaka city in Bangladesh. The findings show that households with proximity to river, higher income, university degree, pro-environmental activities, pro-environmental attitude, worst water quality perception, and higher benefit perception are more likely to pay for the water quality improvement program. The findings based on the Probit model indicate that local residents are willing to pay 17.90 BDT for fishable level and 23.08 BDT for swimmable level (which is higher than the current charge of 11.02 BDT per 1000 liter water). The estimated annual aggregate WTP shows that residents are willing to pay more for the multiple rivers (USD34.8 million) than River Buriganga (USD29.5 million). The findings of this study can be used as a guide for the Dhaka Water and Sewerage Authority (DWASA) to charge the water bill to households and industries. The collections from higher water bill can help the government to finance more wastewater treatment plants to keep the urban rivers clean for sustainable Dhaka city.